Prawa rodzin ofiar przypadków śmierci wymagających wyjaśnienia - Jasudowicz, Tadeusz (Kwartalnik Prawa Publicznego, 2013)
The main aim of the article is the analysis of rights of family member of victims, who’s death requires clarification according to standards set out in international human rights law. The reason for the article is the critical assessment of the investigation carried out in relation to the plane crash in Smolensk that killed Polish President Lech Kaczynski, his wife and a group of high-ranking government officials and other prominent persons. Author – primarily on the basis of the case law of the European Court of Human Rights – discusses the standard of adequate and effective investigation in cases of unclarified death, indicating inter alia such important elements as the independence and fairness of the investigation. Moreover the author points out, according to the emerging case law, the requirement of public control over the investigation. Finally, the analysis includes the right of families to participate in the investigation. In conclusion, the author states that in the case of the investigation into the Smolensk Plane Crash, these standards have been in many ways seriously affected.